Pengembangan Aplikasi Mobile Gateway sebagai Perantara Komunikasi antara Wireless Body Area Network berbasis Protokol Komunikasi Bluetooth Low Energy dan Pusat Data menggunakan Metode Store-Forward - Firman Budi Safrizal; Adhitya Bhawiyuga; Eko Sakti Pramukantoro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Wireless Body Area Network (WBAN) is a wireless network technology that designed to monitor vital signs of human body health. WBAN could remotely check a patient's health condition so that the patient still be able to move freely. However, WBAN sensor devices has resource limitation such as communication capability, computational power, available memory and storage. One primising solution to the problem of process and manage large amount of medical data is to use cloud computing platform. However, WBAN sensor devices are mostly doesn't have ability to connect to internet. In this research, we proposed a gateway to connect between WBAN and cloud storage. The gateway is developed in a mobile platform so that the patient has mobile capability. The gateway also has store-forward mechanism to store and forward the data temporarily when the gateway doesn't have internet connection or lack of network infrastructure. ECG sensor (AD8232) is used in this research. Bluetooth Low Energy is used for sensor-gateway connection and MQTT for gateway-cloud connection.